1992
DOI: 10.1007/bf00024553
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of in vitro wheat somatic embryogenesis

Abstract: A spring wheat genotype which produces somatic embryos in vitro, after short and long-term culture, was tested for its ability to sexually transmit this embryogenic trait . Reciprocal crosses were performed between a embryogenic line and a nonembryogenic variety .Immature embryos were cultured on Murashige and Skoog medium plus 2 mg/12,4-dichlorophenoxyacetic acid, gelled with 5 .5 g/l agarose . Somatic embryogenesis was not expressed in the F,'s . In contrast, from several hundred immature embryos of the F 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Endogenous factors, such as the level of growth regulators within plant explants, together with the interaction between endogenous and exogenous hormones may also influence the embryogenic response [32]. Moreover, the ability to develop somatic embryogenesis was also shown to be under genetic control [33], and particularly in sweet potato, the embryogenic response depended on the genotype [10,14,34]. In this study, the absence of embryogenic response was confirmed for cv.…”
Section: Discussionsupporting
confidence: 53%
“…Endogenous factors, such as the level of growth regulators within plant explants, together with the interaction between endogenous and exogenous hormones may also influence the embryogenic response [32]. Moreover, the ability to develop somatic embryogenesis was also shown to be under genetic control [33], and particularly in sweet potato, the embryogenic response depended on the genotype [10,14,34]. In this study, the absence of embryogenic response was confirmed for cv.…”
Section: Discussionsupporting
confidence: 53%
“…The hexaploid wheat (Triticum aestivum L., 2n = 6x = 42) CS was used as a reference due to its high performances in somatic tissue culture (De Buyser et al, 1992). CS DT and NT lines were provided by S.M.…”
Section: Methodsmentioning
confidence: 99%
“…In plants either individual somatic or gametic cells can give rise to true embryos through in vitro culture. In CS wheat (Triticum aestivum) about 95% of the immature embryos cultured on a simple medium produce embryogenic cultures (De Buyser et al, 1992). Visual observation and histology confirm that the compact, yellowish embryogenic cultures possessed embryos and green areas at their surface and unorganized parts (i.e.…”
mentioning
confidence: 99%
“…Genetic control of regeneration has been reported to vary from dominant effect of nuclear genes in corn (Hodges et al, 1986) to additive gene action in wheat and rice (Lazar et al, 1984;Miah et al, 1985;Quimio and Zapata, 1990). De Buyser et al, (1992), assessed the involvement of few genes controlling regeneration in Brazilian wheat genotypes. The presence of a system exhibiting genetic variation for in vitro regeneration is important for enhancing regeneration responses.…”
Section: Introductionmentioning
confidence: 99%